Metabolic Adaptation of a C-Terminal Protease A-Deficient Rhizobium leguminosarum in Response to Loss of Nutrient Transport - Jun, Dong; Minic, Zoran; Bhat, Supriya V.; Vanderlinde, Elizabeth M.; Yost, Chris K.; Babu, Mohan; Dahms, Tanya E. S. (Frontiers in Microbiology, 2018)
Post-translational modification expands the functionality of the proteome beyond genetic encoding, impacting many cellular processes. Cleavage of the carboxyl terminus is one of the many different ways proteins can be modified for functionality. Gel-electrophoresis and mass spectrometric-based techniques were used to identify proteins impacted by deficiency of a C-terminal protease, CtpA, in Rhizobium leguminosarum bv. viciae 3841. Predicted CtpA substrates from 2D silver stained gels were predominantly outer membrane and transport proteins. Proteins with altered abundance in the wild type and ctpA (RL4692) mutant, separated by 2D difference gel electrophoresis, were selected for analysis by mass spectrometry. Of those identified, 9 were the periplasmic solute-binding components of ABC transporters, 5 were amino acid metabolic enzymes, 2 were proteins involved in sulfur metabolism, and 1 each was related to carbon metabolism, protein folding and signal transduction. Alterations to ABC-binding-cassette transporters, nutrient uptake efficiency and to amino acid metabolism indicated an impact on amino acid metabolism and transport for the ctpA mutant, which was validated by measured amino acid levels.